The influence of an intensive and integrated place-based professional development program on teachers' views of the nature of science - Andrea Rae Milner; Toni A Sondergeld; Charles Rop (Arizona State University, 2014)
Appropriate views of the nature of science are vital to scientific literacy yet rarely taught in US schools primarily due to naïve NOS views held by teachers. Thus, most school teachers need further educational NOS experiences and instruction. Science education literature suggests teachers can learn NOS through both implicit (learning through doing) and explicit (precise utilization) professional development opportunities. Through an integrated field studies teacher professional development program (A River Runs Through It [ARRT]) we implemented both implicit and explicit NOS instruction to see if the combination of methods would improve NOS beliefs following the program. Results obtained from pre and post VNOS-C (see Appendix A) surveys show a modest post-test increase in teachers informed NOS views in all NOS aspects (except Inferential which remained the same), supporting the notion of using both implicit and explicit instruction in teaching the nature of science. In the context of a place-based, field oriented and naturally integrated watershed, our work offers insight into the value of using both implicit experiences and explicit instruction in the teaching of the nature of science for changing participant views of NOS. However, due to the large number of naïve post-test NOS views in Empirical, Theory vs. Law, Inferential, Scientific Method, and Tentative aspects we realize extended NOS experiences and instruction are necessary if science teacher educators expect to elicit dramatic and sustained change in teacher NOS beliefs. Our study demonstrates that the combination of implicit and explicit NOS instructional methods in teacher professional development programs could be a meaningful method of impacting teachers NOS beliefs as we saw an increase in all NOS aspects from pre to post with the exception of one area which remained the same.